Reduced GABAergic inhibition in the basolateral amygdala and the development of anxiety-like behaviors after mild traumatic brain injury. - Camila P Almeida-Suhett; Eric M Prager; Volodymyr Pidoplichko; Taiza H Figueiredo; Ann M Marini; Zheng Li; Lee E Eiden; Maria F M Braga (PLoS ONE, 2014)
Traumatic brain injury (TBI) is a major public health concern affecting a large number of athletes and military personnel. Individuals suffering from a TBI risk developing anxiety disorders, yet the pathophysiological alterations that result in the development of anxiety disorders have not yet been identified. One region often damaged by a TBI is the basolateral amygdala (BLA); hyperactivity within the BLA is associated with increased expression of anxiety and fear, yet the functional alterations that lead to BLA hyperexcitability after TBI have not been identified. We assessed the functional alterations in inhibitory synaptic transmission in the BLA and one mechanism that modulates excitatory synaptic transmission, the α7 containing nicotinic acetylcholine receptor (α7-nAChR), after mTBI, to shed light on the mechanisms that contribute to increased anxiety-like behaviors. Seven and 30 days after a mild controlled cortical impact (CCI) injury, animals displayed significantly greater anxiety-like behavior. This was associated with a significant loss of GABAergic interneurons and significant reductions in the frequency and amplitude of spontaneous and miniature GABAA-receptor mediated inhibitory postsynaptic currents (IPSCs). Decreases in the mIPSC amplitude were associated with reduced surface expression of α1, β2, and γ2 GABAA receptor subunits. However, significant increases in the surface expression and current mediated by α7-nAChR, were observed, signifying increases in the excitability of principal neurons within the BLA. These results suggest that mTBI causes not only a significant reduction in inhibition in the BLA, but also an increase in neuronal excitability, which may contribute to hyperexcitability and the development of anxiety disorders.